What are Households Willing to Pay for Better Tap Water Quality? A Cross-Country Valuation Study - Olivier Beaumais; Anne Briand; Katrin Millock; Céline Nauges (Fondazione Eni Enrico Mattei (FEEM), 2014)
We estimate willingness to pay (WTP) for better quality of tap water on a unique cross-section sample from 10 OECD countries. On the pooled sample, households are willing to pay 7.5% of the median annual water bill to improve the tap water quality. The highest relative WTP for better tap water quality was found in the countries with the highest percentage of respondents being unsatisfied with tap water quality because of health concerns. The expected WTP increased with income, education, environmental concern, and health and taste concerns with the tap water.
Keywords: C24; D12; Q25; Q51; 330; Contingent Valuation; Household Data; Interval Model; Water Quality; Willingness to Pay